Monitoring outcomes of climate smart agricultural options at multiple levels: understanding adoption, synergies and tradeoffs - Bonilla Findji, Osana; Eitzinger, Anton; Bejarano, Gustavo; Ouédraogo, Mathieu; Buah, Saaka S.J.; Zougmoré, Robert B.; Jarvis, Andy (2019)
This framework will support field practitioners in tracking over time, the progress and dynamic changes in adoption of CSA options and their related impacts at household and farm level.